2015
DOI: 10.18632/oncotarget.3771
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of colorectal cancer stem cell survival and invasive potential by hsa-miR-140-5p mediated suppression of Smad2 and autophagy

Abstract: Colorectal cancer (CRC) is the third highest mortality cancer in the United States and frequently metastasizes to liver and lung. Smad2 is a key element downstream of the TGF-β signaling pathway to regulate cancer metastasis by promoting epithelial to mesenchymal transition and maintaining the cancer stem cell (CSC) phenotype. In this study, we show that hsa-miR-140-5p directly targets Smad2 and overexpression of hsa-miR-140-5p in CRC cell lines decreases Smad2 expression levels, leading decreased cell invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 55 publications
10
87
0
Order By: Relevance
“…By targeting various targets, miR-140-5p has shown to critically involve in tumor cell proliferation, apoptosis, vascularization, migration and invasion. These previously confirmed targets includes Sp1 [9], IGF1R [11], MMD [12], HDAC4 [13], Smad2 [14], TGFBR1 [15], FGF9 [15], SOX2 [16], Slug [17], BMP2 [19], Smad3 [20], and ADAMTS5 [21]. Although miR-140-5p is generally accepted as a tumor suppressor, an oncogenic role of miR-140-5p has also been implicated depending on different cell context.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…By targeting various targets, miR-140-5p has shown to critically involve in tumor cell proliferation, apoptosis, vascularization, migration and invasion. These previously confirmed targets includes Sp1 [9], IGF1R [11], MMD [12], HDAC4 [13], Smad2 [14], TGFBR1 [15], FGF9 [15], SOX2 [16], Slug [17], BMP2 [19], Smad3 [20], and ADAMTS5 [21]. Although miR-140-5p is generally accepted as a tumor suppressor, an oncogenic role of miR-140-5p has also been implicated depending on different cell context.…”
Section: Introductionmentioning
confidence: 83%
“…It is encoded within intron 16 of Wwp2, an E3 ubiquitin ligase on chromosome 16 [9]. Expression profiling of tumors and normal tissues has revealed a possible tumor suppressive role for miR-140-5p in many cancers, including ovarian cancer [10], lung cacner [11,12], CRC [13,14], osteosarcoma [13], hepatocellular carcinoma [15], breast cancer [16], esophageal cancer [17] and basal cell carcinoma [18]. By targeting various targets, miR-140-5p has shown to critically involve in tumor cell proliferation, apoptosis, vascularization, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhai et al showed that the tumor formation and metastasis ability of colon cancer stem cells can be abolished by the overexpression of miR-140-5p, which directly affected a target known as Smad2 [15]. In addition, primary tumor tissues showed a progressive loss in miR-140-5p expression as compared with that in normal colorectal mucosa, whereas tissues affected by liver metastasis were associated with a further decreased expression of miR-140-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an elevated miR-140-5p expression was found to be closely related to a better prognosis in stage III and IV CRC patients. In contrast, Mosakhani et al discovered that the up-regulation of miR-140-5p was closely associated with worse overall survival in metastatic CRC patients harboring a wild type KRAS/BRAF [15]. In addition, downregulated miR-140-5p expression was closely related to poorer overall survival, an advanced clinical stage and lymph node metastasis [16].…”
Section: Discussionmentioning
confidence: 99%